Variasi Waktu Bleaching dan Jenis Adsorben untuk Meningkatkan Kualitas Minyak Ikan Silase Bandeng - Hamzah, Nanang; Supriyanto, Supriyanto; Indarto, Cahyo (Universitas Pattimura, 2024)
Milkfish is often processed into various products due to its nutritious and delicious taste. However, these production activities inevitably generate waste in the form of heads, bones, and offal, which are underutilized and contribute to environmental problems. Milkfish waste, which still contains a high-fat content, can be utilized to produce fish oil using the silage method. The pale and clear color of fish oil is one of the factors affecting consumer acceptance. This study aimed to determine the quality of fish oil derived from milkfish silage. Two factors were applied: bleaching time (10, 15, and 20 minutes) and various adsorbents (bentonite, activated carbon, and zeolite), treated as experimental variables. The results showed that the type of adsorbent and the duration of bleaching significantly affected (p<0.05) the quality characteristics of fish oil. The best results in this study were observed in samples subjected to a bleaching time of 20 minutes treatment with zeolite adsorbent, with a yield value of 95.91±0.25%. The color (L) was observed at 34.25±0.40; clarity at 98,35±0,50 %T; specific gravity at 0,833±0,00 g/mL; acid number at 0,28±0,00 mgKOH/g, free fatty acids at 0,13±0,00%, peroxide number at 0,60±0,14 mEq/kg. Overall, all treatments' physical and chemical characteristics, on average, have met the standard quality criteria established by SNI, IFOS, IFOMA, Draft CAC, and Farmakope.